Meteorology - Şen, Zekai (Springer International Publishing AG, 2020)
The root meaning of word meteorology is the science of moving things in the air, which is referred to as the troposphere or the lower layer of atmosphere. Among such things are cloud formation and movement, wind and its speed, particulate matter and aerosol, precipitation (rainfall, snow and hail), temperature and pressure differences, water vapor, which are meteorological variables.
Keywords: Meteorology; Earth Systems Data Processing and Visualization Using MATLAB; Environmental Sciences